2020
DOI: 10.5216/rpt.v48i4.62122
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Awareness of Head Lice Among Elderly Residents in Long-Term Care Facilities in Uberlandia, Mg, Brazil

Abstract: The purpose of this investigation was to determine the occurrence of head lice in long-term care facilities (LTCFs) in Uberlandia, MG, Brazil, analyze associations with sex, ethnicity, age and hair characteristics, and verify awareness among elderly adults. Head inspections were performed and infestation was characterized on individual forms. A questionnaire on the biology, epidemiology and control of head lice was applied. Overall occurrence was 1.4%, being highest in elderly women with medium-length curly ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The selected studies pointed out that the infestation showed variations in the prevalence rates of parasitosis among men and women. However, in seven studies, females obtained the highest proportions of infected people, in studies conducted in Uberlândia 40,[43][44][45][46] , Belo Horizonte 39 and Divinópolis 42 . Only in one of the studies that evaluated the presence of the parasite in hair samples, positivity was higher for males 38 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The selected studies pointed out that the infestation showed variations in the prevalence rates of parasitosis among men and women. However, in seven studies, females obtained the highest proportions of infected people, in studies conducted in Uberlândia 40,[43][44][45][46] , Belo Horizonte 39 and Divinópolis 42 . Only in one of the studies that evaluated the presence of the parasite in hair samples, positivity was higher for males 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the municipality of Manaus (state of Amazonas) showed greater infestation of the parasite in female hair, comprising 27.5% 47 and 3.0% 24 . The higher prevalence of infestations in females may be related to the predominance of medium to long hair among women, a cultural habit verified since childhood in the country 46 . Moreover, medium and long hair present a larger contact surface, facilitating transmission, especially among children while playing 44 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations